Strategi Corporate Societal Marketing (CSR) Blibli Tiket Action dalam Program Cinta Bumi - Angkawibawa, Harla Nathalya; Elkezia, Natasha; Wempi, J.A (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The Cinta Bumi program is part of Blibli's Tiket Action CSR initiative, serving as a tangible action towards sustainability aligned with the Sustainable Development Goals (SDGs). This study applies the Preparation, Engagement, and Perpetuation (PEP) model to explore and analyze the strategies behind the Cinta Bumi program and assess the sustainability strategies implemented by Blibli Tiket Action. The study utilizes a qualitative approach with data collection techniques such as interviews, literature reviews, and document analysis. The research findings indicate that Blibli Tiket Action's implementation of the PEP model has successfully delivered positive impacts, evidenced by the increased recycling of waste and the conversion of used packaging into tree seedlings, as observed through the growing public participation in the Packaging Take Back Program over the years. The study reveals two key findings: effective communication strategies are crucial in delivering information, and many companies in Indonesia implement SDG programs with limited funding, leading to less than optimal results.